If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + 5p = -3p + -31 Combine like terms: -7p + 5p = -2p -2p = -3p + -31 Reorder the terms: -2p = -31 + -3p Solving -2p = -31 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. -2p + 3p = -31 + -3p + 3p Combine like terms: -2p + 3p = 1p 1p = -31 + -3p + 3p Combine like terms: -3p + 3p = 0 1p = -31 + 0 1p = -31 Divide each side by '1'. p = -31 Simplifying p = -31
| 70-30=10+ | | 4x-12+5x=-30 | | 4x^3-4x^2-224x=0 | | 50-40=10+ | | -3v-3=-21 | | 30x+5(2x+y)=0 | | 7x=11+38 | | y=1.75x-1 | | 23-19=135 | | 12m+5=281 | | 7=-2-3n | | 22+8n=54 | | 20+7-4(x+1)= | | 2+7a+7=20+2a | | 10+3h=-6+2h | | -15x^2=12x-5 | | 3a+3b+2a= | | -17=a-3 | | 12x-12=8+6+6x | | m+4=6m-2 | | 2(2x+4)/2= | | -2=1+x | | 65X=31 | | 7+x=9+27 | | 1x+16=1x | | 5x+2(10x)+4(25x)=12.50 | | 11+5e=8+4e | | -6x+1=2x-7 | | 28-4d=-12-3p | | z+n=m | | (r-4)(r+1)+(r-4)(r+6)=0 | | 14+x=5+2x |